2014
DOI: 10.1590/0103-8478cr20140370
|View full text |Cite
|
Sign up to set email alerts
|

Deforming mandibular osteomyelitis in a cow caused by Trueperella pyogenes

Abstract: This study reports an unusual case of deforming mandibular osteomyelitis in a cow caused by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Although it is commensal to the microflora of ruminants and pigs, T. pyogenes is easily isolated from the cutaneous and mucosal tissues of these animals (ROGOVSKYY et al, 2018;GALÁN-RELAÑO et al, 2019). Thus, it is believed that the case described here is directly related to needle reuse for the intramuscular application of drugs in the bovine or the failure to perform antisepsis of the skin at the application site (MOTTA et al, 2011;CAFFARO et al, 2014;MEGID;RIBEIRO;PAES, 2016), as reported by the owner.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although it is commensal to the microflora of ruminants and pigs, T. pyogenes is easily isolated from the cutaneous and mucosal tissues of these animals (ROGOVSKYY et al, 2018;GALÁN-RELAÑO et al, 2019). Thus, it is believed that the case described here is directly related to needle reuse for the intramuscular application of drugs in the bovine or the failure to perform antisepsis of the skin at the application site (MOTTA et al, 2011;CAFFARO et al, 2014;MEGID;RIBEIRO;PAES, 2016), as reported by the owner.…”
Section: Discussionmentioning
confidence: 87%
“…Due to its pyogenic, opportunistic characteristic (taking advantage of a gateway), T. pyogenes causes suppurative infection in domestic and wild animals (RISSETI et al, 2017;ÇEÇEN et al, 2018;ROGOVSKYY et al, 2018), although virulence factors have not been fully elucidated (RISSETI et al, 2017;LIU et al, 2018;TAMAI et al, 2018). The evolution of the disease is related to cases of mastitis, arthritis, interdigital phlebitis, osteomyelitis, abortion, metritis, orchitis, omphalitis and bronchopneumonia as well as subcutaneous abscess or abscess in parenchymal tissues, with a variable prognosis (CAFFARO et al, 2014;ISHIYAMA et al, 2017;WARETH et al, 2018;KONTTURI et al, 2019;PIERSANTI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the cattle, the most common etiologic agent of the lumpy jaw is Actinomyces bovis, but there are reports of lumpy jaw caused by other bacteria, such as Trueperella pyogenes (Caffaro et al, 2014). This study provides the first report of lumpy jaw in a Holstein cow caused by Nocardia farcinica based on the clinical, histopathological and molecular characterization.…”
Section: Introductionmentioning
confidence: 87%
“…Presumptive diagnosis of lumpy jaw is based on clinical signs, and the diagnosis can be confirmed by detection of the etiological organism from the lesion with histopathology (Attaway & Flynn, 2013 ). In the cattle, the most common etiologic agent of the lumpy jaw is Actinomyces bovis , but there are reports of lumpy jaw caused by other bacteria, such as Trueperella pyogenes (Caffaro et al., 2014 ). This study provides the first report of lumpy jaw in a Holstein cow caused by Nocardia farcinica based on the clinical, histopathological and molecular characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Typischerweise wird eine Osteomyelitis des Kieferknochens beim Rind durch die Infektion mit Actinomyces spp. und Eitererregern wie u. a. Trueperella pyogenes hervorgerufen [35] [36]. Bei dieser auch Kieferaktinomykose genannten Erkrankung wölbt sich die Außenfläche des betroffenen Knochens vor und bildet eine harte Auftreibung.…”
Section: Diskussionunclassified